Long-term solid fuel use and risks of major eye diseases in China: a population-based cohort study of 486,532 adults - Chan, KA; Yan, M; Bennett, D; Chen, Y; Yang, L; Du, H; Lam, K; Chen, Z (Public Library of Science, 2021)
Background: Over 3.5 billion individuals worldwide are exposed to household air pollution from solid fuel use. There is limited evidence from cohort studies on associations of solid fuel use with risks of major eye diseases, which cause substantial disease and economic burden globally.